2014
DOI: 10.1016/j.jprot.2014.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1-induced changes in the glioblastoma secretome suggest its role in tumor progression

Abstract: The tumor microenvironment including glial cells and their inflammatory products regulates brain tumor development and progression. We have previously established that human glioma cells are exquisitely sensitive to IL-1 stimulation leading us to undertake a comparative analysis of the secretome of unstimulated and cytokine (IL-1)-stimulated glioblastoma cells. We performed label-free quantitative proteomic analysis and detected 190 proteins which included cytokines, chemokines, growth factors, proteases, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 100 publications
3
37
0
Order By: Relevance
“…The gradient of cytokines in our analysis definitely point at an intratumoral source of cytokine release although the BAT area also contributes. Secretomic data from cultured tumor and astrocytic cells clearly indicates that these are capable of producing various cytokines including those highlighted in the present study [33, 34]. Nevertheless accumulated data and our immunohistochemistry results strongly imply that the overwhelming source of secreted inflammatory cytokines emanate from myeloid cell, either infiltrating macrophages or resident microglia and that myeloid cells are the drivers of other early features of reaction as astrocyte gliosis [5, 35, 36].…”
Section: Discussionsupporting
confidence: 49%
“…The gradient of cytokines in our analysis definitely point at an intratumoral source of cytokine release although the BAT area also contributes. Secretomic data from cultured tumor and astrocytic cells clearly indicates that these are capable of producing various cytokines including those highlighted in the present study [33, 34]. Nevertheless accumulated data and our immunohistochemistry results strongly imply that the overwhelming source of secreted inflammatory cytokines emanate from myeloid cell, either infiltrating macrophages or resident microglia and that myeloid cells are the drivers of other early features of reaction as astrocyte gliosis [5, 35, 36].…”
Section: Discussionsupporting
confidence: 49%
“…Although some studies on GBM secretome[26,27,28,29] (which includes shedded microvesicles, apoptotic bodies and other secretory vesicles) have been previously reported, our study focuses solely on the effects of proinflammatory cytokines on the protein cargo of discrete secretory vesicles - exosomes. Exosomes differ from other secretory vesicles in that they are endosomal in origin and result due to release of ILVs into extracellular milieu by fusion of MVBs with the plasma membrane[30,31].…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 targets suppressor of cytokine signaling (SOCS) proteins potentially leading to overactive Stat3, a transcription factor important in glioma progression [31][34]. Our recent GBM secretome study also revealed that IL-1 upregulates secretory molecules implicated in glioma progression such as MMP2, tenascin-C, galectin-1, pentraxin 3, IL-8 and MCP-1, while (down)modulating numerous extracellular matrix (ECM) and ECM-modulating proteins [14]. These results together suggest that IL-1 controls crucial aspects of glioma signaling and progression.…”
Section: Introductionmentioning
confidence: 96%